Futility of Centor Score (CS) for Predicting Group A Streptococcal (GAS) Pharyngitis in an Adult Hyper-endemic Native American (NA) Population. (4th October 2017) - Close, Ryan; McAuley, James B
Abstract: Background: Prevalence of GAS pharyngitis among adults is 5% to 15% in the general population. Methods using clinical criteria and laboratory testing to diagnose GAS have not been evaluated in Native American (NA) populations with a higher prevalence than the general population. Methods: Prompted by an apparent increase (10–15× above national rates) in invasive GAS in 2016 we began a comprehensive epidemiologic study of GAS. Part of this evaluation included GAS pharyngitis. From January to March 2017, we collected a Centor score (CS), throat swab for culture and rapid antigen test (RAT) for all adults ≥18 years presenting with sore throat. For comparison, we also reviewed our electronic health record (EHR), identifying all adults with RAT on file from Jul. to December 2016. Results: From July to December 2016, 224 (33.5%) adults with sore throat had a positive RAT. From January to March 2017, 268 adults had RAT and culture performed: 86 (32.1%) and 85 (31.7%) were positive by RAT and culture, respectively. Comparing adults 18–44 years and ≥ 45 years, odds of culture positive GAS pharygnitis for young age group were 2.00 (CI 1.06–3.88, P = 0.023). RAT alone was 75.4% sensitive and 88.0% specific. Comparing adults18–44 years to ≥ 45 years, RAT alone was less sensitive (70.1% vs. 94.4%) and less specific (86.6% vs. 90.6%) in the younger group. Comparing RAT plus CS to RAT alone, the addition of CS did not significantly change specificity (91.3% vs. 88.0%) or sensitivity (74.7% vs. 75.3%). A higher CS increased the odds of a positive GAS culture. Tonsillar exudates (89.9%) and fever (51.9%) were the most and least sensitive criteria, respectively. Absence of cough (50%) and tonsillar exudates (23.3%) were the most and least specific criteria, respectively. Conclusion: GAS was confirmed in > 30% of cases by RAT on both retrospective review of the EHR and prospectively via RAT or culture. These rates are significantly higher than what is reported in general population. Young age was associated with culture positive GAS. The high sensitivity of exudates and high specificity of absence of cough indicates these criteria may be helpful in deciding which adults are most likely to have GAS. Higher CS did increase odds of GAS positive culture, but the addition of CS to RAT did not significantly alter sensitivity or specificity in this population. Disclosures: All authors: No reported disclosures.